Evaluation of Candida Score: a bedside scoring system for early antifungal therapy in non-neutropenic critically ill patients - Dash, Chinmaya; Pal, Abhinanda; Sinha, Sulekha (International Journal of Advances in Medicine, 2019)
Background: Invasive Candida infections are the most common invasive fungal infections. Multiple site colonization plays a major role. Further decrease in host immunity (e.g. neutropenia, diabetes mellitus etc.) aggravates local invasion and dissemination which finally leads to candidemia. Hence the study was done to evaluate “Candida Score” in non-neutropenic critically ill patients for early antifungal therapy. Methods: In this prospective observational cohort study, all critically ill patients having sepsis or septic shock on admission or during their stay in ICU stay were included in the study. The components of “Candida Score” like severe sepsis, total parenteral nutrition, surgery, and multifocal Candida colonization were as per Leone et al. Clinical sepsis was given score of 2 if present and 0 if absent. The other variables were given score 01 if present and 0 if absent. The score more than 2.5 is considered significant. Results: Out of 78 patients admitted in the ICU a total of 26 blood culture positives were reported. The prevalence of Candidemia (based on culture) was 23.1% (n=06). The strains isolated were Candida non albicans (n=4, 66.7%) and Canida albicans (n=2, 33.3%). Candida was isolated in different samples other than blood culture of 26(33.33%). The most common specimen with Candida isolation was from urine (n=14, 60.87%), followed by endotracheal aspiration and sputum (n=3, 13% each) and BAL fluid (n=1, 04.3%). Among the isolates Candida non albicans (n=12, 52.2%) was more prevalent than Candida albicans (n=11, 47.8%). The prevalence was maximum for the age group of 60 to 69 years (42.31%) followed by 70 to 79 yrs and 50-59 yrs. Among all patients, 14 patients were referred in our hospital and 12 of them had a prolonged ICU stay (>10 Days). The patients with the Candida score ≥2.5 were 06 in numbers, of which 66.7% were having score 3 followed by one each of having score 4 and 5. Out of these 06 patients 04 received antifungal treatment. One patient with Candida score more than 03 succumbed to death without having antifungal treatment. Conclusions: Early identification of invasive candidiasis with the use of “Candida Score” in critically ill patients may help to initiate antifungal interventions and even help the treating physician or intensivist to formulate the more effective treatment algorithms.